Typing of methicillin resistant and sensitive Staphylococcus aureus isolated from Tamilnadu, India using DNA fingerprints by pulsed-field gel electrophoresis - Rajaduraipandi, Kathirvel; Morrison, Donald; Mani, Mariappa; Nambirajan, Guruvu; Panneerselvam, Kanesan; Shobana, Coimbatore Subramanian; Narendran, Venkatapthy; Manikandan, Palanisamy (Acta Biologica Szegediensis, 2014)
MRSA infection is alarming particularly in hospital set ups/community. We typed 43 isolates of Staphylococcus aureus (MRSA and MSSA) based on genomic DNA restriction fragment length polymorphisms (RFLPs). The genomic DNA of the test isolates was digested with SmaI enzyme, fractionated by PFGE and the patterns were assessed by dendrogram for percentage similarity. The SmaI restricted genomic DNA of 19 MRSA and 24 MSSA identified 27 different PFGE patterns, in which 11 and 16 were from MRSA and MSSA, respectively. Prevalence predominance was observed in few types/subtypes of MSSA (type B and subtype I-1) and MRSA (sub type A-2) and high percentage of similarity was noticed among the subtypes of PFGE types such as P and I of MSSA. During the epidemiological studies, to understand the dissemination of endemic/epidemic MRSA and MSSA, PFGE-based typing of pathogens may be used as a reliable and effective typing method.